LICENCIAMENTO AMBIENTAL MUNICIPALIZADO COMO INSTRUMENTO DE PRESERVAÇÃO AMBIENTAL E DE PROMOÇÃO DO DESENVOLVIMENTO SUSTENTÁVEL URBANO - Costa, Ana Paula Ronzani (2010)
In recent years the procedure of environmental licensing or renewal has become extremely important, as appears as a tool for environmental planning of a preventive nature of environmental damage. This work aims to verify whether the environmental licensing process municipalized can be used as an instrument to prevent environmental and sustainable urban development. In this aspect will be addressed the main legal provisions governing the matter, presenting a critical analysis of the licensing process in Brazil, in view of their duties and powers, and finally we will address the process of decentralization of environmental licensing. It is expected to finish the work more clearly the pros and cons of decentralization by analyzing the experience of some states of the Federation.